Structural Features of Lignin Fractionated From Industrial Furfural Residue Using Alkaline Cooking Technology and Its Antioxidant Performance - Li, Rui; Wang, Xiaohui; Lin, Qixuan; Yue, Fengxia; Liu, Chuanfu; Wang, Xiaoying; Ren, Junli (Frontiers in Energy Research, 2020)
Furfural, a versatile platform compound, is produced from the hydrolysis of pentose (hemicellulose) in lignocellulosic biomass. The manufacturing of furfural results in the production and accumulation of cellulose- and lignin-rich furfural residue, simultaneously. Reasonable and effective utilization of furfural residue would provide both environmental and economic benefits. In this work, alkali cooking technology was applied to extract lignin from industrial furfural residue. The effects of different alkali treatment conditions on the composition and chemical structure of extracted lignin and solid residue were studied. The results showed that extracted lignin contained abundant guaiacyl (G), syringyl (S), and p-hydroxyphenyl (H) structural units, among which the G-type lignin structural unit accounted for the main proportion. The extracted lignin samples were rich in hydroxyl, and the highest content of hydroxyl was 4.02 mM/g under the condition of T3 (135°C−0.35 M). An oxidize resistance test showed that extracted lignin showed a high inhibition effect on DPPH. The increase of lignin content in solid residue was due to the carbonization of cellulose into a lignin-like substance under the condition of a high temperature alkali treatment. This alkali cooking technology is suitable for extracting lignin from furfural residue, which has a promising application as a potential antioxidant in the food and cosmetic industry.